Frontal white matter association with sleep quality and the role of stress. (14th June 2022) - Bruce, Heather A.; Kochunov, Peter; Kvarta, Mark D.; Goldwaser, Eric L.; Chiappelli, Joshua; Schwartz, Adina; Lightner, Samantha; Endres, Jane; Yuen, Alexa; Ma, Yizhou; Van der vaart, Andrew; Hatch, Kathryn S.; et al.
Summary: An important measure of brain health is the integrity of white matter connectivity structures that link brain regions. Studies have found an association between poorer sleep quality and decreased white matter integrity. Stress is among the strongest predictors of sleep quality. This study aimed to evaluate the association between sleep quality and white matter and to test if the relationship persisted after accounting for stress. White matter microstructures were measured by diffusion tensor imaging in a population of Old Order Amish/Mennonite ( N  = 240). Sleep quality was determined by the Pittsburgh Sleep Quality Index. Current stress levels were measured by the perceived stress scale. Exposure to lifetime stress was measured by the lifetime stressor inventory. Microstructures of four white matter tracts: left and right anterior limbs of internal capsule, left anterior corona radiata, and genu of corpus callosum were significantly correlated with sleep quality (all p  ≤ 0.001). The current stress level was a significant predictor of sleep quality ( p  ≤ 0.001) while lifetime stress was not. PSQI remained significantly associated with white matter integrity in these frontal tracts (all p  < 0.01) after accounting for current stress and lifetime stress, while current and lifetime stress were not significant predictors of white matter in any of the four models. Sleep quality did not have any substantial mediation role between stress and white matter integrity. Sleep quality was significantly associated with several frontal white matter tracts that connect brain structures important for sleep regulation regardless of current or past stress levels.